MUSTALAHUL HADIS ILMINING SHAKLLANISHI VA RIVOJLANISHI (HIJRIY IV ASRDAN XII ASRGACHA) - Mustafoyev Abubakr Muhiddin o‘g‘li (Journals Park Publishing, 2022)
This article discusses the next three periods of the development and development of the "mustalahul event" field from the fourth to the 12th century. From writing extensive books in the field of mathematics to stagnation in the field of events, the development of events has been thoroughly explained. Also, the achievements and stages of development achieved in this area at every given time are based one by one on the opinions expressed by scientists. In those days, the great scholars who served in the field of mathematics, their news, and their invaluable works were highlighted.
Keywords: interpretation, great event, mustalahul event, art, text, cylinder, presenter, writer.